Determination of Bismuth by Electrothermal Atomic Absorption Spectrometry using Single Drop Micro Extraction in Real Samples - Chamsaz, M.; Arbab-Zavar, M.H.; Riazi, M.M.; Takjoo, R. (Asian Journal of Chemistry, 2011)
A novel and extremely sensitive method for extraction and determination of bismuth in aqueous samples by liquid phase micro extraction (LPME) combined with electrothermal atomic absorption spectrometry using a new ligand is described. In this method Bi3+ in pH 6 during 20 min extraction time at 20 ºC is reacted with S-methyl-3-salicylidene dithiocarbazate dissolved in 4 μL of chloroform micro drop. After extraction, the micro drop was retracted and directly transferred into a graphite tube coated by palladium and tungsten with co-injection of tartaric acid as chemical modifier. In this investigation the type of organic solvent, volume of organic solvent, pH, temperature and extraction time were optimized. Using 10 mL sample solution an enrichment factor of 100 was obtained. The detection limit was calculated to be 19 pg mL-1 based on 3Sb and relative standard deviation for five replicate analysis of 0.5 ng mL-1 Bi3+ was 4.8 %. The calibration curve was liner in the range of 19 pg mL-1 to 2.4 ng mL-1 with a sensitivity of 4.0 pg mL-1. This method was used for determination of bismuth in tap water, waste water, sea water, soil and reliability of the method was evaluated using two reference materials.